Unsteady free convection flow and heat transfer towards a shrinking sheet with radiation effects - Md. Ali, Fadzilah; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (2012)
In this paper, the problem of unsteady free convection boundary layer flow past a vertical axisymmetric permeable shrinking sheet in the presence of radiation effect is studied. The governing system of partial differential equations is transformed into ordinary differential equations by using the similarity transformation, which is then solved numerically using the shooting method. The effects of the governing parameter, namely the radiation parameter on the skin friction coefficient, the local Nusselt number, and the temperature profiles are investigated. It is found that the dual solutions exists for non-zero radiation. It is also observed that when a high radiation parameter is applied, the variations in the temperature distribution become less significant.